Making electricity subsidies work: Cross-country lessons for Philippine energy policy - Kris A. Francisco; Patricia Thea A. Basilio (Philippine Institute for Development Studies (PIDS), 2025)
Electricity subsidies serve diverse policy goals but pose significant fiscal, efficiency, and equity challenges. This paper focuses on the Philippines' three major electricity subsidy mechanisms, which includes the Universal Charge for Missionary Electrification (UCME), Lifeline Rate, and Senior Citizen Discount, and situates their design and outcomes within a broader international evidence base. We synthesize recent empirical work from peer-reviewed journals and international organizations to identify design features associated with improved efficiency and equity. We center on prevalent mechanisms such as increasing block tariffs, cross-subsidy mechanisms, time-variant pricing, and targeting approaches. Our systematic review analyzes how these mechanisms perform across contexts and examines transferability to the Philippine setting, given the country's institutional capacity, political economy constraints, and electricity market structure. Our key findings highlight recurring design flaws including fiscal sustainability pressures, leakage and mis-targeting of benefits, and regressive distribution patterns, as well as effective practices such as targeted, transparent, and administratively feasible reforms that align subsidies with intended vulnerable groups. The paper concludes with implications for policy design, implementation, and future research directions, emphasizing the value of international lessons to inform fiscally sustainable and socially equitable electricity subsidies in the Philippines.
Keywords: 330; Electricity Subsidies; Philippine Energy Market; Subsidy Reform